ELECTROCARDIOGRAPHIC PROFILE OF DILATED CARDIOMYOPATHY IN PATIENTS ATTENDING A TERTIARY CARE HOSPITAL OF WESTERN NEPAL - Kafle, Ram Chandra; Paudel, Navaraj; Sharma, Dibya; Alurkar, Vijaya Madhav (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION:  Cardiomyopathy is a disease  of the heart  muscle  that  leads  to deterioration of myocardial functioning.  It has different morphological variation with  dilated cardiomyopathy being the most common  form  comprising over 90% of all cases. Heart  failure  (HF)  is the  most  common  clinical  presentation of dilated  cardiomyopathy.   Various  electrocardiographic changes  are common in these patients.  The most common  cause of sudden death in these patients is arrhythmia.  This study aimed at characterizing different  electrocardiographic changes  in patients of dilated cardiomyopathy admitted  for heart failure.MATERIAL AND METHODS: A retrospective analysis of records of admitted  patients  from l" January 2015 to 30th April 2018 was conducted.  Study was conducted  after obtaining ethical clearance  from institutional review  board. Data was collected in a preformed proforma and analyzed using SPSS 20.0 version.RESULTS: Consecutive  400 cases of dilated  cardiomyopathy with systolic dysfunction (LVEF